Social relationships and empowerment as risk factors for anemia among anxious pregnant women in Pakistan - Suleman, Nadia; Liaqat, Rakhshanda; Park, Soim; Ahmad, Ikhlaq; Zaidi, Ahmed; Atif, Najia; Kamran, Haris; Rahman, Atif; Surkan, Pamela J.; Malik, Abid (Journal of Maternal and Child Health, 2026)
Background: Empowered women with social support are more likely to seek healthcare services, leading to better health outcomes. This study investigated spousal relationships, social support, and women's empowerment in relation to anemia in pregnant women living in urban areas of Rawalpindi, Pakistan.Subjects and Method: A cross-sectional study enrolled 1,200 pregnant women at ≤ 22 weeks of gestation from Holy Family Hospital, Pakistan. The anxiety component of the Hospital Anxiety and Depression Scale (HADS) was used to assess eligibility, with a cutoff score of > 8. The quality of marital relationships, social support, and women's empowerment were evaluated using the MacArthur Relationship Questionnaire (MRQ), the Multidimensional Scale of Perceived Social Support (MSPSS), and an empowerment scale, respectively. Blood samples were collected to assess anemia in the participants. Descriptive statistics, risk ratios and bivariate analysis were conducted to explore the association.Results: At enrollment, 29.7% of pregnant women exhibited mild anemia, 14.6% exhibited moderate anemia, and 0.3% exhibited severe anemia. Having a strong spousal relationship was significantly associated with decreased risk of anemia (RR=0.87; 95% CI= 0.82 to 0.93, p<0.001). However, social support from family members (excluding spouses) or friends did not show a significant association with the risk of anemia. Interestingly, financially empowered pregnant women had a higher risk of anemia compared to women who were not financially empowered (RR=1.14; 95% CI= 1.01 to 1.30; p= 0.040).Conclusion: Support from a husband was associated with reduced risk of anemia in pregnant women in Pakistan. Enhancing spousal relationships and incorporating health literacy into empowerment programs could improve maternal health by lowering the risks of anemia.